Active force cancellation of a near resonance vibrating system using robust H∞ control. (1st January 2012) - Fok, S.C.; Lau, M.W.S.; Seet, G.L.; Low, E.
In this study, the active force cancellation performance of a robust H∞ controller is investigated on a near resonance vibrating system consisting of a rotating machine hard mounted on a flexible base. This configuration and phenomenon can be present in vehicle engine mounts. The model of the vibrating system was first identified experimentally. The uncompensated system frequency response is then used to design the controller. The control objective is to reduce the system (RMS) gain. The effectiveness of the controller has been demonstrated experimentally through implementation on a digital signal processor. Results show reductions of the measured RMS transmitted forces at different mount locations when the machine is operated at speeds near the principal mode of vibration. However at frequency where the vibration is not significant, the reduction in transmitted force level can be minimal.